Development of a PjBL-Based Science Project Teaching Module on the Material of Living Things and Their Environment to Improve Students' Scientific Literacy State Vocational School 1 Modoinding - Yunita Meylan Kumajas; Anatje Lihiang; Jovialine Albertine Rungkat; Herry Sumampouw (Riset : Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to develop a Project Based Learning (PjBL) based Science Project module on the subject of living things and their environment that meets the criteria of validity, practicality, and effectiveness and is able to improve students' scientific literacy. This study is a research and development (R&D) using the ADDIE model which includes the stages of Analysis, Design, Development, Implementation, and Evaluation. The study was conducted at SMK Negeri 1 Modoinding. The results of the study indicate that the PjBL-based Science Project module developed meets the criteria of very validity based on the assessment of material experts and media experts. The module also received positive responses from teachers and students so that it is included in the category of very practical for use in learning. In addition, the application of the module is able to support the implementation of project-based learning well and contribute to improving students' scientific literacy. In conclusion, the PjBL-based Science Project module on the subject of living things and their environment developed through the ADDIE model is suitable for use in learning because it meets the criteria of validity, practicality, and effectiveness and can improve students' scientific literacy. Keywords: PjBL, Science Project Module, Living Things and Their Environment, Science Literacy.